ANALISIS MINAT BELAJAR SISWA SEKOLAH DASAR PADA PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MEDIA SCRATCH - Nabila Aulia Chaerunnisa; Martin Bernard (IKIP Siliwangi, 2021)
This research was conducted to analyze the learning interest of elementary school students in learning mathematics using scratch media. The research used descriptive qualitative method. The research subjects were 15 elementary school students in Cimahi for the 2020-2021 school year. The research provides a test instrument with the provision of a student learning interest scale questionnaire, test and interviews. Scratch is a programming language that can be used as a learning medium in the form of games, quizzes, animations and others. The result indicate of the questionnaire data, students' interest in learning has a percentage of 73.25%. All data in this research were processed using Microsoft Excel by finding average of indicator of student interest in learning. Baesed on the result of this research, it was shown that elementary school students’s interest in learning mathematic using scratch falled into strong category.